2020
DOI: 10.3390/plants9040525
|View full text |Cite
|
Sign up to set email alerts
|

Low-Copy Genes in Terpenoid Metabolism: The Evolution and Expression of MVK and DXR Genes in Angiosperms

Abstract: Terpenoids are a diverse class of metabolites that impact plant metabolism in response to environmental cues. They are synthesized either via a predominantly cytosolic (MVA) pathway or a plastidic pathway (MEP). In Arabidopsis, several enzymes from the MVA and MEP pathways are encoded by gene families, excluding MVK and DXR, which are single-copy genes. In this study, we assess the diversity, evolution and expression of DXR and MVK genes in selected angiosperms and Coffea arabica in particular. Evolutionary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
3
5
0
Order By: Relevance
“…Interestingly, we found that the terpene pathway follows this trend as it was found to be more highly expressed at the yellow stage than at the red stage. This could indicate that terpenes are predominantly formed at the yellow stage in agreement with an earlier observation [ 73 ] that showed a decreased expression of the early terpene biosynthetic gene DXR during the final stage of fruit development. Similarly, it was found that the phenylpropanoid pathway was more expressed at the yellow stage [ 71 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, we found that the terpene pathway follows this trend as it was found to be more highly expressed at the yellow stage than at the red stage. This could indicate that terpenes are predominantly formed at the yellow stage in agreement with an earlier observation [ 73 ] that showed a decreased expression of the early terpene biosynthetic gene DXR during the final stage of fruit development. Similarly, it was found that the phenylpropanoid pathway was more expressed at the yellow stage [ 71 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, it was found that the phenylpropanoid pathway was more expressed at the yellow stage [ 71 ]. Nevertheless, even though all studied C. arabica genotypes followed the same developmental trend, they differed in their level of expression of the members of the terpene pathway, suggesting that genotype specific differences underpin the strength of volatile terpene biosynthesis in C. arabica in agreement with earlier suggestions from Silva et al 2020 [ 73 ].…”
Section: Discussionsupporting
confidence: 88%
“…Plants were selected based on size uniformity and were transferred to pots containing 3 L of aerated nutrient solution (ANS), adapted from Clark, 1975 ) by de Carvalho et al (2013) . The experiment was carried out as described in Silva et al (2020) , under controlled temperature (23 ± 2°C) and light/dark cycle (12h/12h, photosynthetically active photon flux density of ∼400 μmol m −2 .s −1 ). The following treatments were applied: (a) ANS (control); (b) ANS + hexanoic acid (Merck, final concentration 0.55 mM) for 48 h. Three plants per pot were grown into six plastic pots in which three pots received each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative polymerase chain reaction (Q-PCR) is a fast and effective technique for detecting and quantifying bacteria and fungi and monitoring their gene expression in natural ecosystems [16]. Q-PCR tests were used to measure the expression levels of regulatory genes in biosynthetic pathways in different organisms [17][18][19]. iTRAQ (isobaric tags for relative and absolute quanti cation) have a high coverage and can accurately and sensitively detect and quantify low-abundance, cytoplasmic, membrane, nuclear, and extracellular proteins using the isotopelabeled amino groups of peptides and LC-MS/MS [20,21].…”
Section: Introductionmentioning
confidence: 99%